NATIONALISM-ORIENTED INTERACTIVE MATERIALS FOR NEWS ITEMS LEARNING IN JUNIOR HIGH SCHOOL - Ixsir Eliya (Universitas Negeri Makassar, 2020)
The values of nationalism can be integrated into instructional materials as a way to achieve competence standards set by the government. This study aimed to produce nationalism-oriented interactive materials for news item learning in junior high school. This study employed a research and development design that consisted of seven stages, including data analysis, product design, prototype development, expert validation, product revision, small-group tryout, and final model revision. The result of the analysis showed that the interactive materials could meet the teacher’s and students’ needs in learning news item and the development of the product was in line with the principle of instructional material development. The interactive instructional materials were packaged in a compact disk (CD) containing an application called Macromedia Flash. The values of nationalism integrated in the instructional materials include the pride in the national language which is Indonesian Language, the love for the country, the spirit of preserving national songs, heroism, discipline, and hard work. These values were embedded in the form of visual, audio, or audiovisual media that can be displayed in the classroom and thus used to study listening.